2006
DOI: 10.1249/01.mss.0000227641.68360.c2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Pedometer Used by the Elderly with the FFT Algorithm

Abstract: We suggest that our FFT method is suitable for estimating the number of steps during walking in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Previous studies have also reported difficulties in obtaining accurate step counts at slow and high walking speeds [8, 14, 31, 32]. A small number of studies report good accuracy for all walking speeds [14, 20, 21, 31]. However, many of these studies do not specify gait velocities and refer to them as ‘slow, normal, or fast-paced’, while studies that specify gait velocities look at smaller ranges starting at 0.5 to 0.9 m/s [14, 32] and don’t exceed 2 m/s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported difficulties in obtaining accurate step counts at slow and high walking speeds [8, 14, 31, 32]. A small number of studies report good accuracy for all walking speeds [14, 20, 21, 31]. However, many of these studies do not specify gait velocities and refer to them as ‘slow, normal, or fast-paced’, while studies that specify gait velocities look at smaller ranges starting at 0.5 to 0.9 m/s [14, 32] and don’t exceed 2 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in walking speed and the ability to vary cadence demonstrate increased function level [18], reduced risk, and higher predictions of survival [17, 19]. While a small number of studies have shown that results from the methods they used are not affected by different walking speeds, accuracy during shuffling, stair climbing, and jogging have yet to be investigated and only limited gait velocity ranges are examined [14, 20, 21]. Furthermore, the use of step counts as a measure of physical activity is limited as the characteristics of the steps are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported 84% adherence with adults age 60 years and over and just 60–62% adherence for subjects of ages 12 to 39 years in a study involving a hip-located ActiGraph worn for four days (Troiano et al , 2008), which offers room for improvement. In addition to adherence issues, many studies have reported reduced accuracy of many step counting devices at lower gait velocities (Dijkstra et al , 2008; Ryan et al , 2006; Le Masurier and Tudor-Locke, 2003; Greene et al , 2010; Ichinoseki-Sekine et al , 2006). Individuals with reduced physical or cognitive function, who present greater issues with adherence, often walk at slower gait velocities.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of adaptivity means that the settings need to be calibrated per individual and may result in an overestimation of step counts in the free-living environment (Bassett Jr and John, 2010). We have previously developed a step detection algorithm with adaptive thresholds using an AM system consisting of four accelerometers (waist, right thigh, and bilateral ankles) and demonstrated that, unlike other algorithms or devices used in other studies (Dijkstra et al , 2008; Ryan et al , 2006; Le Masurier and Tudor-Locke, 2003; Greene et al , 2010; Ichinoseki-Sekine et al , 2006), it performs with acceptable accuracy at slow gait velocities, even as low as 0.1 m/s, in addition to normal and fast walking speeds, and under simulated free-living conditions without requiring calibration (Fortune et al , 2014a). However, an algorithm which can perform accurately at a number of locations using a minimal number of AMs would be beneficial in cases where subject adherence may be an issue.…”
Section: Introductionmentioning
confidence: 99%
“…the step frequency (SF). Algorithms based on Autocorrelation (AC) 7,8 and Power Spectral Density (PSD) 9 have been used to this end. These methods require analysis of data collected over a time window (TW) of a given size.…”
Section: Introductionmentioning
confidence: 99%